Victimization of Youth and its Prevention - Rendón Cárdenas, Alma Eunice (Trabajo Social UNAM, 2017)
In this article we pose the importance of prevention in order to try to reduce the levels of victimization in all spheres of an individual’s socialization: home, school, among friends or members of the community. However, in matters of prevention it is impossible to start from a deterministic position and affirm that a person will become a delinquent due to the simple fact that he/she has been exposed to one of the risk factors during his childhood or youth, even when referring to episodes of reiterated victimization. The propensity to repeat patterns of violence or incur in acts of delinquency in the future is a result of exposition to a large variety of risk factors throughout various stages in a person’s lifetime. We will address various theories on the relationship between victimization, violence and delinquency. Then we shall provide data on the situation of victimization in Mexico today, above all based on the recently published Survey of Social Cohesion for the Prevention of Violence and Delinquency and the National Survey of Victimization, 2015. Finally, we will discuss the various ways in which the matter of victimization has been approached from the policy of social prevention of violence and delinquency, identifying challenges and opportunities for the future.